2019
DOI: 10.1038/s41598-019-50136-w
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress-dependent and -independent death of glioblastoma cells induced by non-thermal plasma-exposed solutions

Abstract: Non-thermal atmospheric pressure plasma has been widely used for preclinical studies in areas such as wound healing, blood coagulation, and cancer therapy. We previously developed plasma-activated medium (PAM) and plasma-activated Ringer’s lactate solutions (PAL) for cancer treatments. Many in vitro and in vivo experiments demonstrated that both PAM and PAL exhibit anti-tumor effects in several types of cancer cells such as ovarian, gastric, and pancreatic cancer cells as well as glioblastoma cells. However, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 56 publications
(50 reference statements)
0
39
0
Order By: Relevance
“…In this work, we produced a PA-RL through a multiwire plasma source, whose main innovative feature is its ability to work without the use of a technical gas, while allowing to treat 20 mL of liquid [28,[34][35][36]. Moreover, the source architecture we here propose can be easily scaled in order to produce volumes of activated solution higher than 20 mL.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this work, we produced a PA-RL through a multiwire plasma source, whose main innovative feature is its ability to work without the use of a technical gas, while allowing to treat 20 mL of liquid [28,[34][35][36]. Moreover, the source architecture we here propose can be easily scaled in order to produce volumes of activated solution higher than 20 mL.…”
Section: Discussionmentioning
confidence: 99%
“…Tanaka et al [26] first proposed the use of RL, whose simple composition (NaCl, KCl, CaCl 2 and lactate) makes it adoptable for the production of PAL, avoiding the possible influence of more organic medium components on its final biological effect [27]. It has been demonstrated that plasma-activated Ringer's Lactate solutions (PA-RL) exhibit an anti-tumor effect in lung, mammary, ovarian cancer cells as well as in glioblastoma in vitro [25,26,28], and in pancreatic and cervical cancer in vivo [26,29]. Several studies demonstrated that the effects of PA-RL may be ascribed to RONS, together with the activation of lactate [26,28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the mechanism of ICD induction associated with the different physical and chemical agents is not fully elucidated, a common theme is the induction of the oxidative and endoplasmic reticulum (ER) stress in exposed cells. [ 54,60,68–73 ] NTP has gained increasing attention over the last decade as being a highly controllable mechanism of delivering oxidative species to targets. The pioneering research by Lin et al in 2017 first described NTP as a tool to enhance immunogenicity of cancer cells through the induction of the ER stress.…”
Section: Nonthermal Plasma (Ntp) As An Immunogenic Cell Death Inducermentioning
confidence: 99%
“…In a recent study, Tanaka et al [ 84 ] examined the differences in intracellular molecular mechanisms of the effects of PAM and plasma‐activated Ringer's lactate solution (PAL) in U251SP cells. They showed that PAM generates higher ROS in U251SP cells than PAL.…”
Section: Action Mechanism Of Cap In Glioblastoma Tumorsmentioning
confidence: 99%